1993
DOI: 10.1073/pnas.90.5.2060
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of primary plasmacytomas requires stromal cell feeder layers.

Abstract: Attempts to grow primary murine plasmacytomas in vitro have, to date, been largely unsuccessful. In this study, we demonstrate that long-term in vitro growth of primary plasmacytomas is accomplished by using feeder layers composed of stromal cells from the initial site of plasmacytomagenesis. The early neoplastic lines established in this manner are dependent on physical contact with the stromal layer, which is mediated in part by CD44, for growth and survival. The stromal cells provide at least two stimuli fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…12,33 The bone marrow microenvironment is critical for myeloma cell survival and proliferation. [34][35][36][37] In addition, the bone marrow microenvironment has been reported to protect myeloma cells from chemotherapy. 38,39 We have shown that patient myeloma cell growth is dependent on human bone marrow microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…12,33 The bone marrow microenvironment is critical for myeloma cell survival and proliferation. [34][35][36][37] In addition, the bone marrow microenvironment has been reported to protect myeloma cells from chemotherapy. 38,39 We have shown that patient myeloma cell growth is dependent on human bone marrow microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experiments could demonstrate some growth of 5T2 MM in vitro when co-cultured with a stromal cell layer (consisting of bone marrow fibroblasts) (unpublished data). In contrast, 5T33 MM cells grow in a stroma-independent fashion (Degrassi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Degrassi (1993) demonstrated that the interaction of CD44 with its ligand hyaluronate was responsible for part of the adhesion of plasmacytomas on stromal cell layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The apparent promotion of 5Ј-C /c-myc + clones in IL-6 transgenic BALB/c mice can be added to the body of evidence on the significance of IL-6 for plasmacytomagenesis in conventional BALB/c mice. [24][25][26] Furthermore, the finding that BALB/c mice homozygous for an IL-6-null allele (BALB/c.IL-6 −/− ) were completely resistant to plasmacytomagenesis induced by the pristane 27 and the Myc and Raf expressing retrovirus, J3V1, 28 established that IL-6 plays a unique and requisite role in both inflammation-induced and virally induced plasmacytoma development. Subsequent studies with another retrovirus that constitutively co-expressed Abl and Myc revealed an important mechanism by which IL-6 facilitates plasmacytomagenesis, the cooperation with Myc.…”
Section: Tablementioning
confidence: 99%